2023
DOI: 10.1093/jscr/rjad034
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary meningioma with associated multiple micronodules: a case report and literature review

Abstract: Primary pulmonary meningioma (PPM) is a rare and benign slow growing tumor with good prognosis. It often presents as an asymptomatic, well-circumscribed, solitary pulmonary nodule. Wedge resection is the management of choice for both diagnosis and treatment. Here, we report one case of PPM with increased fluorodeoxyglucose (FDG) uptake and associated micronodules, which was clinically suspicious for malignancy. The patient was a 60-year-old female who presented with persistent shortness of breath for 1 year. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Patients with PPMs and MPMNs usually present with no obvious symptoms, other than some atypical respiratory symptoms, although this can depend on tumor size, location, and accompanying diseases[ 5 - 7 ]. PPMs are usually found through imaging examinations[ 5 , 8 ]. Patients with PPMs are mainly middle-aged or older women[ 1 , 7 , 9 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with PPMs and MPMNs usually present with no obvious symptoms, other than some atypical respiratory symptoms, although this can depend on tumor size, location, and accompanying diseases[ 5 - 7 ]. PPMs are usually found through imaging examinations[ 5 , 8 ]. Patients with PPMs are mainly middle-aged or older women[ 1 , 7 , 9 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
“…The vast majority of PPMs are benign, well-circumscribed and solitary, with a favorable prognosis[ 5 , 10 - 12 ]. Therefore, the major therapeutic method for PPM is surgery, such as wedge resection or lobectomy[ 8 , 10 , 13 , 14 ]. It has also been suggested that a conservative approach, using close medical monitoring, is the best option for patients when the location, size, and number of smaller nodules challenge the accessibility for biopsy or resection[ 13 , 15 ].…”
Section: Clinical Features Of Ppm and Mpmnmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 70 patients (including our case) have been diagnosed with PPM and reported in the English literature. 1,2 Most PPMs are benign (0.4-6.5 cm in diameter), but five malignant PPMs (1.5-15 cm) have been reported. Radiologically, a PPM typically presents as an isolated, well-defined solid nodule 1 ; however, some PPMs may present as ground-glass density nodules or multiple solid nodules.…”
mentioning
confidence: 99%